Molecular pump functioning due to fluctuations of intramembrane potential - Корочкова, Таисия Евгеневна; Машира, Василий Александрович; Шкода, Наталия Григорьевна; Розенбаум, Виктор Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper considers a model of the molecular pump, which creates a directed motion of nanoparticles through the cell membrane, at the edges of which the preset concentrations are maintained due to fluctuations of intramembrane potential. For this model, the numerical solution of equations for the particle flow at the stochastic switching of two sawtooth potentials with given switching frequencies is obtained. This solution has allowed to determine the dependence of the particle flow and concentration ratio at the membrane edges at zero flow on such system parameters as temperature, spatial amplitude and the fluctuation frequency of the potential profile. Also, low-frequency asymptotics is obtained, which has allowed to compare the mechanisms of molecular pump and motor, operating in the same mode of the potential energy fluctuations, namely in the high-temperature region, the particle flow through the membrane greatly exceeds the particle flow of motor with parameters, corresponding to the considered pump. Furthermore, it is found that the pump can function in the mode of potential energy sign fluctuations whereas such operation is prohibited for the corresponding motor. These patterns are caused by the difference in the boundary conditions of the pump and motor: setting concentrations on the membrane edges for the pump and periodic boundary conditions for the motor.